Efektifitas Penggunaan Modifikasi Miniature of Vulcano Disaster Management terhadap Kesiapsiagaan Perawat dalam Penanggulangan Bencana Erupsi Gunung - Arif Mulyadi; Andi Hayyun Abiddin; Agus Khoirul Anam; Anggraini Khodijahturrohmah (Universitas Malahayati Lampung, 2023)
ABSTRACT Volcanic eruption is one of the threats of disaster in Indonesia. Nurses as the largest part of health workers in the region have a very important role during a disaster as the front line in health services for disaster victims.To identify the effectiveness of the use of modification of Miniature of Vulcano Disaster Management on nurse preparedness in disaster management of volcanic eruptions.This study uses a Quasi-Experimental Pretest-Posttest design. The sample in this study were 25 nurses who were in the Mount Kelud Eruption Disaster-Prone Area, Blitar Regency, which were carried out by means of quota sampling. The results showed that there was an increase in nurses' understanding of preparedness in dealing with volcanic eruptions as indicated by a change in the mean score at pretest from 57 to 86 after posttest. Wilcoxon test results showed a value of 0.000 (0.05). The use of Miniature of Vulcano Disaster Management media is effective in increasing nurse preparedness in dealing with volcanic eruption disasters. Keywords: Disaster, Eruption, Education, Nurse ABSTRAK Erupsi gunung berapi adalah salah satu ancaman bencana di Indonesia. Perawat sebagai bagian terbesar tenaga kesehatan yang berada di daerah mempunyai peran sangat penting saat bencana sebagai lini terdepan dalam pelayanan kesehatan pada korban bencana. Mengidentifikasi efektifitas penggunaan modifikasi Miniature of Vulcano Disaster Management terhadap kesiapsiagaan perawat dalam penanggulangan bencana erupsi gunung. Penelitian ini menggunakan desain Quasi-Experimental Pretest-Posttest. Sample dalam penelitian ini adalah perawat yang berada di Kawasan Rawan Bencana Erupsi Gunung Kelud Kabupaten Blitar sebanyak 25 orang yang dilakukan dengan cara kuota sampling. Hasil penelitian menunjukkan bahwa terdapat peningkatan pemahaman perawat tentang kesiapsiagaan dalam penanggulangan bencana erupsi gunung yang ditunjukkan dengan perubahan rerata skor saat pretest 57 menjadi 86 setelah postest. Hasil uji Wilcoxon menunjukkan nilai 0.000 ( 0,05). Penggunaan media Miniature of Vulcano Disaster Management efektif dalam meningkatkan kesiapsiagaan perawat dalam penanggulangan bencana erupsi gunung berapi. Kata Kunci: Bencana, Erupsi, Edukasi, Perawat